A rapid differential display analysis of nasal swab fingerprints to distinguish allergic from non‐allergic rhinitis subjects by mesoporous silica particles and MALDI‐TOF mass spectrometry - Lombardo, Nicola; Preianò, Mariaimmacolata; Maggisano, Giuseppina; Murfuni, Maria Stella; Messina, Luigi; Pelaia, Girolamo; Savino, Rocco; Terracciano, Rosa (Proteomics (Weinheim), 2017)
Discriminating different rhinitis cases can sometimes be difficult as the diagnostic criteria used to identify the various subgroups are not always unambiguous. The nasal fluid (NF) highly reflects the pathophysiology of these inflammatory diseases. However, its collection, as nasal lavage fluid, may cause discomfort. Due to the non‐invasiveness and rapidity of collection, nasal swab might represent an alternative to overcome these problems and also an ideal source of biomarkers. In this study, we demonstrate that the combined use of mesoporous silica (MPS) with MALDI‐TOF MS allows the rapid detection of differential nasal peptide profiles from nasal swabs of healthy (H), allergic rhinitis (AR) and non‐allergic rhinitis (NAR) subjects. NF peptides from nasal swabs were captured by the mean of MPS then profiled by MALDI‐TOF MS. As a proof‐of‐principle, we also explored the ability of our platform to discriminate between nasal swabs of patients with AR and NAR, and between these groups and H controls. Four peaks resulted differentially expressed between NAR and AR, two peaks discriminated AR from H while one peak segregated NAR from H group. Therefore, peptides selected and enriched by our platform could form a part of a diagnostic ‘‘rhinomic’’ profile of the allergic and non‐allergic patients.